2021
DOI: 10.3390/agronomy11112164
|View full text |Cite
|
Sign up to set email alerts
|

High Frequency Direct Organogenesis, Genetic Homogeneity, Chemical Characterization and Leaf Ultra-Structural Study of Regenerants in Diplocyclos palmatus (L.) C. Jeffrey

Abstract: Diplocyclos palmatus (L.) C. Jeffrey, commonly referred to as “Shivalingi” or “Lollipop climber” is a valuable medicinal plant with a climbing growth habit used in traditional medicine. It is reputed to have antiarthritic, anti-diabetic properties and to be useful in various skin and reproductive problems. Overexploitation of wild plants and low seed germination have resulted in the decline of the species in the wild. Thus, the present investigation was aimed to establish an effective in vitro propagation proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 48 publications
1
2
0
Order By: Relevance
“…The increase in photosynthetic pigment content witnessed the functional health of the photosystem to various light spectra. Similar kinds of findings have also been reported in other plants, such as D. arayalpathra (Ahmad et al, 2018a), D. salicifolia (Ahmad et al, 2018b), and Diplocyclos palmatus (Upadhyay et al, 2021).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The increase in photosynthetic pigment content witnessed the functional health of the photosystem to various light spectra. Similar kinds of findings have also been reported in other plants, such as D. arayalpathra (Ahmad et al, 2018a), D. salicifolia (Ahmad et al, 2018b), and Diplocyclos palmatus (Upadhyay et al, 2021).…”
Section: Discussionsupporting
confidence: 86%
“…Our findings were in accordance with a previous report on C. equisetifolia (Duhoux et al, 1986 ). The synergistic effect of BA and NAA has been demonstrated by various workers, such as in D. salicifolia (Ahmad et al, 2018b ), Dendrobium anosmum (Nguyen et al, 2022 ), and Diplocyclos palmatus (Upadhyay et al, 2021 ). However, contrary to our results, BA in combination with IAA was found most suitable nutrient media for optimum shoot proliferation from the nodal segment of D. arayalpathra (Ahmad et al, 2018a ) and A. salviifolium (Pandey et al, 2022 ).…”
Section: Discussionmentioning
confidence: 93%
“…Plant tissue culture offers an excellent technological foundation for the quick and efficient production of phytochemical substances for commercial purposes [13,59]. It is likely that ex-vitro-established micropropagated plants' increased production of phytochemical substances is attributable to a variety of factors, including the media they are growing in, the explants they are using, their genotype, and even the PRGs they have added to the medium [60,61]. Our findings are in line with previous studies that found that micropropagated plants had more phytochemicals than their donor plants, such as Clerodendrum thomsoniae [62], Hemidesmus indicus [63], Tecoma stans [64], Hildegardia populifolia [65], and Diplocyclos palmatus [61].…”
Section: Discussionmentioning
confidence: 99%